Sequencing chromosome 5D of Aegilops tauschii and comparison with its allopolyploid descendant bread wheat (Triticum aestivum) - Akpinar, Bala A; Lucas, Stuart J; Vrána, Jan; Doležel, Jaroslav; Budak, Hikmet (Plant biotechnology journal, 2015)
Flow cytometric sorting of individual chromosomes and chromosome-based sequencing reduces the complexity of large, repetitive Triticeae genomes. We flow-sorted chromosome 5D of Aegilops tauschii, the D genome donor of bread wheat and sequenced it by Roche 454 GS FLX platform to approximately 2.2x coverage. Repetitive sequences represent 81.09% of the survey sequences of this chromosome, and Class I retroelements are the prominent type, with a particular abundance of LTR/Gypsy superfamily. Nonrepetitive sequences were assembled to cover 17.76% of the total chromosome regions. Up to 6188 nonrepetitive gene loci were predicted to be encoded by the 5D chromosome. The numbers and chromosomal distribution patterns of tRNA genes suggest abundance in tRNA(L) (ys) and tRNA(M) (et) species, while the nonrepetitive assembly reveals tRNA(A) (la) species as the most abundant type. A comparative analysis of the genomic sequences of bread wheat and Aegilops chromosome 5D indicates conservation of gene content. Orthologous unique genes, matching Aegilops 5D sequences, numbered 3730 in barley, 5063 in Brachypodium, 4872 in sorghum and 4209 in rice. In this study, we provide a chromosome-specific view into the structure and organization of the 5D chromosome of Ae. tauschii, the D genome ancestor of bread wheat. This study contributes to our understanding of the chromosome-level evolution of the wheat genome and presents a valuable resource in wheat genomics due to the recent hybridization of Ae. tauschii genome with its tetraploid ancestor.
Keywords: Triticum; Genes, Plant; Chromosome Mapping; comparative genomics; molekulární sekvence - údaje; pšenice; chromozomy rostlin; Gene Order; Models, Biological; Chromosomes, Plant; D genome donor of wheat; biologické modely; mapování chromozomů; Molecular Sequence Data; chromosome 5D; Polyploidy; rostlinné geny; pořadí genů; polyploidie